2017
DOI: 10.1016/j.nima.2016.09.051
|View full text |Cite
|
Sign up to set email alerts
|

High precision momentum calibration of the magnetic spectrometers at MAMI for hypernuclear binding energy determination

Abstract: We propose a new method for absolute momentum calibration of magnetic spectrometers used in nuclear physics, using the time-of-flight (TOF) differences of pairs of particles with different masses. In cases where the flight path is not known, a calibration can be determined by using the TOF differences of two pair combinations of three particles. A Cherenkov detector, read out by a radio frequency photomultiplier tube, is considered as the high-resolution and highly stable TOF detector. By means of Monte Carlo … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…A Cherenkov detector, read out by a RFPMT, was considered as the high-resolution and highly stable TOF detector. By means of Monte Carlo simulations it was demonstrated that the magnetic spectrometers at the MAMI electron-scattering facility can be calibrated absolutely with an accuracy 𝛿 𝑝/𝑝 ≤ 10 −4 , which will be crucial for high precision determination of binding energies of the Λ particle in the nuclear ground state [21].…”
Section: Rft and Rfpmt: Applications In Nuclear Physicsmentioning
confidence: 99%
“…A Cherenkov detector, read out by a RFPMT, was considered as the high-resolution and highly stable TOF detector. By means of Monte Carlo simulations it was demonstrated that the magnetic spectrometers at the MAMI electron-scattering facility can be calibrated absolutely with an accuracy 𝛿 𝑝/𝑝 ≤ 10 −4 , which will be crucial for high precision determination of binding energies of the Λ particle in the nuclear ground state [21].…”
Section: Rft and Rfpmt: Applications In Nuclear Physicsmentioning
confidence: 99%
“…1. The tracking detector package of 𝐻𝜋𝑆 is the same as before, but an ultra-high precision timing detector, based on Cherenkov radiators coupled to Radio Frequency Photomultiplier Tubes (RF PMT) [15] will be added. The expected time resolution of such detectors is better than 10 ps, FWHM.…”
Section: Decay Pion Spectroscopy Of the λ-Hypernuclei: A New Approachmentioning
confidence: 99%
“…The RF PMT-Cherenkov detector will also provide an absolute momentum calibration of the 𝐻𝜋𝑆 by measuring the time-of-flight (TOF) differences of pairs of particles with different masses [15]. Monte Carlo simulations demonstrated that the magnetic spectrometers at the MAMI electron-scattering facility can be calibrated absolutely with an accuracy δp/ p ≤ 10 −4 , which will be crucial for high precision determination of hypernuclear masses [15].…”
Section: Decay Pion Spectroscopy Of the λ-Hypernuclei: A New Approachmentioning
confidence: 99%
See 1 more Smart Citation